Effects of selected mesophilic Lactobacillus strains obtained from camel milk on the volatile and sensory profiles of a model short-ripened pressed cows' milk cheese. (October 2020) - Belkheir, Khadidja; Zadi-Karam, Halima; Karam, Nour-Eddine; Carballo, Javier; Centeno, Juan A.
Abstract: Four Tetilla-type cheeses were made in duplicate from pasteurised cows' milk. A control cheese was manufactured with a mesophilic commercial dl -starter only, and the other three cheeses were made with the same starter plus (i) an adjunct culture of a high-diacetyl producer Lactobacillus plantarum strain obtained from camel milk, (ii) an adjunct culture of a peptidolytic Lactobacillus brevis strain isolated from the same source, or (iii) a combination of both adjuncts. After 28 days of ripening, the abundance of the volatiles acetic acid, hexanoic acid, ethyl butanoate and ethyl hexanoate, as well as the scores for flavour preference were significantly ( P  < 0.05) higher in the cheeses made with the two adjuncts than in the control cheeses. The results suggest that the use of selected mesophilic Lactobacillus strains obtained from camel milk as adjunct cultures could differentiate the volatile profile and the sensory quality of short-ripened pressed cows' milk cheeses.